Early life conditions, time preferences, and savings - Effrosyni Adamopoulou; Mattia Colombo; Eleftheria Triviza (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2024)
This study examines how early-life exposure to food scarcity influences individuals' long-term time preferences and savings behavior. To this end, we analyze hand-collected historical data on livestock availability during World War II at the provincial level, alongside detailed survey data on elicited time preferences and household savings. By leveraging differences across cohorts and provinces in a difference-in-differences framework, we find that individuals who experienced more severe scarcity during early childhood develop higher levels of patience later in life and tend to hold more (precautionary) savings, conditional on income. Our findings suggest that exposure to protein scarcity during the first years of life and in utero can instigate a lasting increase in prudent behavior in the form of a coping mechanism.
Keywords: D14; N44; 330; patience; precautionary savings; scarcity; early life experiences